Hacking the brain: Gene therapy as a tool to combat epilepsy - Ng, Maxwell; Bilimoria, Krish; Brar, Karanbir; Pandey, Nikesh (The Meducator, 2021)
Hacking the brain: Gene therapy as a tool to combat epilepsy